The Microeconomic Growth - Liang, Meng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book primarily discusses what could make the economy remain stable and increase the level of coordination, both on the demand and supply side, a fascinating question for economists. In this context, it systematically analyzes the theory of consumption and production growth. Most of the existing economic growth theories fail to analyze consumption growth. That oversight is remedied here, greatly enhancing the usefulness of economic growth theory. Factors influencing consumption and production at the micro scale provide the foundations of the analyzing frame. An economic system with endogenous technological progress can most likely only be rapidly coordinated under market conditions similar to those in a monopoly competition market. Over the course of the work, readers will discover that there is another way of viewing the economic world which is different from regular textbooks.
Key Factors of Economic Growth -- Commodity, Utility Density, Quality and Labor -- Consumption and the Growth of Consumption -- Organization$1 (Bprotection and restriction -- Production Theory- Individuals and Manufacturers -- Analyze of Economic Growth.s
Keywords: Economics; Microeconomics; Economics/Management Science; Microeconomics; Economic Theory